方程$y'+2y = x e^{-x}$的通解为
A: $e^{-2x} + C (x-1)$
B: $C e^{-2x} + (x+1)e^{-x}$
C: $C e^{-2x} + C (x-1) e^{-x}$
D: $Ce^{-2x} + (x-1)e^{-x}$
A: $e^{-2x} + C (x-1)$
B: $C e^{-2x} + (x+1)e^{-x}$
C: $C e^{-2x} + C (x-1) e^{-x}$
D: $Ce^{-2x} + (x-1)e^{-x}$
举一反三
- 函数\(y = {e^{ - {x^2}}}\)的导数为( ). A: \( - 2x{e^{ - {x^2}}}\) B: \(2x{e^{ - {x^2}}}\) C: \( - 2x{e^ { { x^2}}}\) D: \(2x{e^ { { x^2}}}\)
- 下列函数为偶函数的是( )。 A: \( y = {2{e}^{2x}} - {2{e}^{ - 2x}} + \sin x \) B: \( y = {\log _a} { { 1 - x} \over {1 + x}} \) C: \( y = { { {e^x} + {e^{ - x}}} \over 2} \) D: \( y = 3{x^2} - {x^3} \)
- 已知齐次方程$(x-1){{y}^{''}}-x{{y}^{'}}+y=0$的通解为$Y={{C}_{1}}x+{{C}_{2}}{{e}^{x}}$,则方程$(x-1){{y}^{''}}-x{{y}^{'}}+y={{(x-1)}^{2}}$的通解是( ) A: ${{\text{C}}_{1}}x+{{\text{C}}_{2}}{{e}^{x}}-({{x}^{2}}+1)$ B: ${{\text{C}}_{1}}x+{{\text{C}}_{2}}{{e}^{x}}-({{x}^{3}}+1)$ C: ${{\text{C}}_{1}}x+{{\text{C}}_{2}}{{e}^{x}}-{{x}^{2}}$ D: ${{\text{C}}_{1}}x+{{\text{C}}_{2}}{{e}^{x}}-{{x}^{2}}+1$
- 下列函数为偶函数的是( )。 A: \( y = e^{2x} - {e}^{ - 2x} + \cos x \) B: \( y = {\log _2} { { 1 + x} \over {1 -x}} \) C: \( y = 3{x^4} - {x^3} \) D: \( y = { { {e^x} + {e^{ - x}}} \over 2} \)
- 函数\( y = {e^x} \)是微分方程\( y'{e^{ - x}} + {y^2} - 2y{e^x} = 1 - {e^{2x}} \)的解。